Determinants of temporal changes in galectin-3 level in the general population: Data of PREVEND. (1st November 2016) - van der Velde, A. Rogier; Meijers, Wouter C.; van den Heuvel, Edwin R.; Bakker, Stephan J.; van Gilst, Wiek H.; van der Harst, Pim; Hillege, Hans; de Boer, Rudolf A.
Abstract: Background: High baseline galectin-3 levels are associated with increased risk for adverse cardiovascular outcomes in the general population, but determinants of changes in galectin-3 levels over time have not been established. Therefore, we aimed to identify determinants of (temporal) change in galectin-3 levels. Methods: Galectin-3 plasma levels were measured in a large community based cohort (PREVEND study) at 3 different time points: at baseline, after ~ 4 and ~ 9 years. The association of baseline clinical and biochemical factors and (temporal) changes in galectin-3 level was assessed using multivariable mixed-effects regression modeling. Results: In 4355 subjects, galectin-3 plasma levels were available at all time points (mean age: 48 ± 12 years; 50% female). Median galectin-3 level at baseline was 10.7 [8.9–12.7] ng/mL which gradually increased to 11.5 [9.4–14.3] ng/mL after ~ 9 years. Using mixed-effects regression modeling, we first validated as independent determinants of baseline circulating galectin-3: eGFR (chi square (χ 2 ):210.27, p < 0.0001), gender (χ 2 :43.85; p < 0.0001), BMI (χ 2 :19.68, p = 0.0001), NT-proBNP (χ 2 :18.76, p = 0.0001) and serum (total) cholesterol (χ 2 :8.63, p = 0.01). Furthermore, we identified urinary albumin excretion (χ 2 :34.03, p-value: < 0.0001) and systolic blood pressure (χ 2 :16.81, p = 0.002) as independent determinants of temporal changes of galectin-3. Conclusions: In the general population, urinary albumin excretion > 30 mg/24 h and systolic blood pressure > 170 mmHg were identified as significant determinants of dynamic increases in galectin-3 levels over time. These results implicate that treatment of high blood pressure might be effective to prevent increasing galectin-3 levels and its associated conditions.